Pemanfaatan Aplikasi Android untuk Penjadwalan Mata Pelajaran SMK Media Informatika: Utilization of Android Applications for Scheduling SMK Media Informatika Subjects - Syarif, Achmad; Rahdiana, Ikhsan; Hayati, Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This abdimas activities partnered with the SMK Media Informatika which is located at Jl. Sustainable 2 No. 99 Petukangan Selatan Deplu Complex Pesanggrahan South Jakarta 12270. The partners problems are Scheduling subjects still done manually, understanding of mobile programming such as interface design (UI/UX), database design and the technicalities of making Android programs which are still not yet in-depth from each teacher. This problem was overcome through this community service activity in the form of using an Android application for scheduling school subjects, namely providing training to teachers on designing the Android application interface (UI/UX), designing the required database and how to make the scheduling Android application. This activity was carried out face to face at the SMK Media Informatika. From the results of the evaluation questionnaire for the implementation of this activity, 100% of participants stated that this activity was useful, easy to understand, ran effectively and met expectations. So it can be concluded that this activity can provide solutions to the problems experienced by partners.